1985
DOI: 10.1002/cne.902390110
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of adult‐formed granule neurons of the rat olfactory bulb

Abstract: The population dynamics of internal granule cells in the rat olfactory bulb during adult life were analyzed in histological sections and in autoradiograms with (1) counts of granule cells, (2) counts of labeled granule cells 1 month after injection of 3H-thymidine at various ages, and (3) counts of labeled granule cells at varying survival times (up to 18 months) after injection at 3 months and 24 months. The total number of granule cells increases linearly throughout life, approximately doubling between 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
4

Year Published

1997
1997
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(94 citation statements)
references
References 22 publications
3
87
0
4
Order By: Relevance
“…We also found IGF-II mRNA expressed in the olfactory bulb, as has been observed in chicken and mammals (Ayer-Le Lièvre et al, 1991;Lee et al, 1993). Again, adult neuronal recruitment is well documented in this area (Altman, 1969;Kaplan et al, 1985;Lois and Alvarez-Buylla, 1994) and seems to be regulated by behavior (Corotto et al, 1994). Conversely, no new neurons are added to the cerebellum of adult songbirds, where we detected IGF-II expression, or to the cerebellum of adult rodents (Altman and Bayer, 1993), where IGF-I is expressed and necessary for the acquisition of a simple learning paradigm (Castro-Alamancos and Torres-Aleman, 1994).…”
Section: Functional Implications Of Igf-ii In Other Areas Of the Brainsupporting
confidence: 85%
“…We also found IGF-II mRNA expressed in the olfactory bulb, as has been observed in chicken and mammals (Ayer-Le Lièvre et al, 1991;Lee et al, 1993). Again, adult neuronal recruitment is well documented in this area (Altman, 1969;Kaplan et al, 1985;Lois and Alvarez-Buylla, 1994) and seems to be regulated by behavior (Corotto et al, 1994). Conversely, no new neurons are added to the cerebellum of adult songbirds, where we detected IGF-II expression, or to the cerebellum of adult rodents (Altman and Bayer, 1993), where IGF-I is expressed and necessary for the acquisition of a simple learning paradigm (Castro-Alamancos and Torres-Aleman, 1994).…”
Section: Functional Implications Of Igf-ii In Other Areas Of the Brainsupporting
confidence: 85%
“…This local proliferation decreases thereafter, becoming insignificant in adults, and leaving the SVZ/RMS production site as the unique source providing neuroblasts during later stages. Previous studies have reported a higher rate of postnatal proliferation in the SVZ compared with the local production within the OB (Hinds, 1968;Altman, 1969;Kaplan et al, 1985;Frazier-Cierpial and Brunjes, 1989), but none have determined the relative contribution between the two sites. Our finding indicates that most postnatally generated neurons are produced at locations caudal to the bulb and subsequently migrate forward.…”
Section: Sites Of Production and Migration Rates Of Newborn Neurons Amentioning
confidence: 95%
“…In line with this, granule cells, among the key elements for generating LFP oscillations, undergo a permanent renewal (Altman, 1969). Up to 80,000 newborn cells populate the OB per day (Kaplan et al, 1985) (for review, see Peterson, 2002). It would thus be of great interest to evaluate the impact of this neuronal recruitment on odor information processing and to understand how such processing remains constant in a dynamic network.…”
Section: ␥ Oscillations and Olfactory Information Processingmentioning
confidence: 97%